Resistencia De Materiales-Ingeniería Mecánica Estudio De Caso: Degradación Del Acero Astm A36 Sometido Al Fenómeno De Termofluencia - Reyes, Jorge Isaías Caicedo; Chávez, Javier Enrique Orna; Sampedro, Otto Fernando Balseca; Pérez, Diego Fernando Mayorga; Nuñez, Edwin Fernando Viteri; Bernal, Catalina Margarita Verdugo (European Scientific Journal, ESJ, 2017)
Creep is the simultaneous combination of load and high temperature for a time period in a material, and in which mechanical behavior is a new field of research. In this paper, the results of the experimental study are discussed in order to obtain information on the effect of the microstructural level, which resulted in the degradation of ASTM A36 steel affect of moderate effort (1223.14 Kg/cm2 ) in a temperature range of 500 to 650 ° C. The methodology is analytical, qualitative, quantitative, deductive logic and experimental. The tests were conducted according to ASTM E139 using flat specimens which section is reduced and sized according to ISO 6892: 1998 (E). In the tested specimens, samples were extracted from the fractured zone in order to conduct metallographic and micro hardness tests. The results showed that at the temperature of 500ºC in a maximum of 3-day test, the material did not show any significant microstructural level transformations, but from 550ºC to 650 °C it clearly showed the effects of creep in the material microstructural level, both by the presence of cavity characteristics, which are due to the movement of dislocations, like the level of hardness by the formation of soft phases.